Increased inhibition following negative cues: A possible role for enhanced processing. (January 2020) - Okon-Singer, Hadas; Henik, Avishai; Gabay, Shai
Abstract: Based on findings showing that attention is captured by aversive stimuli, previous studies have hypothesized that inhibition of return (IOR) is reduced at spatial locations previously occupied by threat cues. Yet evidence for this view is limited: Only a few studies have demonstrated a reduced degree of IOR following threat cues, while most have not found differences in IOR between aversive and neutral cues. In contrast to previous studies that used the spatial cuing paradigm and for the most part employed mild negative stimuli as cues, we examined the influence of highly aversive, colored and complex pictures of real life situations. As opposed to the stimuli used in previous studies, these pictures are thought to result in enhanced processing as well as in specific enhancement for threat pictures in comparison to neutral ones. Based on evidence indicating that enhanced processing of spatial cues results in increased IOR, we hypothesized that the negative picture cues employed in the present study would yield increased IOR. This hypothesis was confirmed in two experiments. We suggest that the enhancement of IOR following highly threatening cues may be related to efficient spatial orienting of attention in response to stimuli that are important from an evolutionary point of view. The results are discussed in the context of neurocognitive mechanisms that may underlie the modulation of IOR by emotional information.